O pensamento das sensações em O livro do desassossego - Pellegrini, Karen Cristina Teixeira (2022)
This research seeks to explore the ways that the Book of Disquiet gives the body to understand the study of sensations in the Fernando Pessoa’s field. From the theoretical texts of Fernando Pessoa and philosophers such as José Gil and Gilles Deleuze, it is possible to perceive that the Book of Disquiet is a great sensation study, which allows us to open up other ways of thinking about consciousness, art, the book format. The thesis is developed in themes; each one seeking to be small fields of experience, demonstrating in which ways the Book allows intensifying a thought that does not seek representation, but that analyzes sensation and teases it displacements in literature and life